Prognostic implications of CD-57 expression in oral squamous cell carcinoma cases - Santosh Kumar; Akhilesh Chandra; Rahul Agrawal; Priyanka Singh; Meetu Pallavi (Wolters Kluwer Medknow Publications, 2023)
Natural killer (NK) cells are one of the most important effector T -lymphocytes having antitumor effect. Only a few studies are present in the literature, correlating the expression of cluster of differentiation 57 (CD-57) in NK cells in oral squamous cell carcinoma (OSCC). To analyze the effect of the presence of NK cells in the stroma of OSCC and their effect on the tumor progression and prognosis. A retrospective study was performed over 122 OSCC patients who had undergone surgical treatment between 2014 and 16. Wax blocks were obtained and subjected to immunohistochemical (IHC) analysis for CD-57 expression. Patients were followed up for 3 years and 100 cases were finally included in the study and divided into three groups. The association between variable were studied through the Chi-square test, Kruskal-Wallis test, and Mann-Whitney U test. A total of 91% of cases showed positive staining for CD-57. Maximum positive expression (96.6%) was observed in the patients who were alive and without recurrence (Group-II) as compared to dead patients (Group-I) and in well-differentiated squamous cell carcinoma (WDSCC) cases (96.8%) than in poorly differentiated cases. Also, the mean CD-57 positive cells count was found to be highest in Group-II and WDSCC cases. A significant correlation was observed between CD-57 expression and patients' health status. As the expression of CD-57 increased in the tumor stroma of OSCC, the chances for the patient to be alive were increased; therefore, it may serve as a good prognostic marker.